Exploring the Impact of Traditional Games on Children's Motor Skills Development: A Literature Review - Saefullah, Rifki; Pirdaus, Dede Irman; Ismail, Muhammad Iqbal Al-Banna (Research Collaboration Community (Rescollacom), 2024)
This study explores the potential of traditional games in enhancing children's motor skills, focusing on eye-hand-foot coordination. Through a comprehensive literature review, various traditional games were identified, including Boy-Boyan, Fireball, Lato-lato, Blowgun, Sipak Rago, Post Box, Gatrik, Throwing Bananas, Stilts, Clogs, Spinning Top, Throw the Can, Marbles, Clap Stick, Sorolok Rifle, Bekel Ball, Kite, Chicken Feather Football, Angklek, and Pleto. Each game involves different coordination aspects, contributing to the development of children's motor skills. This study highlights the importance of preserving traditional games as cultural heritage and promoting their role in children's physical development.